A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial to Investigate the Effects of Kamishoyosan, a Traditional Japanese Medicine, on Menopausal Symptoms: The KOSMOS Study. (26th February 2021) - Takamatsu, Kiyoshi; Ogawa, Mariko; Obayashi, Satoshi; Takeda, Takashi; Terauchi, Masakazu; Higuchi, Tsuyoshi; Kato, Kiyoko; Kubota, Toshiro
Abstract : Objective . The KOSMOS study, a multicenter, randomized, double-blind, placebo-controlled trial, investigated the effects and safety of kamishoyosan (TJ-24), a traditional Japanese medicine, in the treatment of climacteric disorder. Methods . Japanese women with climacteric disorder were administered a placebo during a 4-week run-in period, after which they were classified as placebo responders (R group) if their score on the modified Questionnaire for the Assessment of Climacteric Symptoms in Japanese Women (m-QACS) with excitability and irritability as the primary outcome improved by ≥ 3 points and as placebo nonresponders (NR group) otherwise. Members of the NR group were randomly allocated to receive either TJ-24 or placebo. After 12 weeks, their m-QACS scores, anxiety and depression, sleep, and overall quality of life (QOL) were compared. Results . The TJ-24 and placebo arms in the NR group included 20 patients each. The change in the m-QACS scores of members of the NR group for excitability and irritability at 12 weeks versus baseline was –3.1 ± 1.7 in the TJ-24 arm, a significant decrease, but compared with –2.7 ± 2.2 in the placebo arm, no significant difference was between two arms. However, the proportion of participants whose score improved by ≥3 points was significantly higher in the TJ-24 arm. In the subgroup analysis of premenopausal women, the changes in the score for excitability and irritability were significantly larger in the TJ-24 arm. The incidence of adverse drug reactions or adverse events did not differ between the two arms, and no serious events were reported. Conclusion . Although no significant difference was identified for the primary outcome, a significantly higher proportion of patients who received TJ-24 displayed improvement. Its high level of safety and effects on excitability and irritability in premenopausal women suggest that TJ-24 may be a useful treatment.